KNOWLEDGE AND ATTITUDE OF ELEMENTARY SCHOOL TEACHERS TOWARDSADHD IN THE KINGDOM OF SAUDI ARABIA (CAHIERS MAGELLANES-NS, 2024)
Background: ADHD is typically affecting school performance, concentration, and self-control atschool. Teachers are often the first ones to suspect ADHD in their students, because they are with themfor most of the day and they know how normal students typically behave in classroom situations.Objectives: The aim of this study is to measure the knowledge level and to assess the attitude towardattention-deficit hyperactivity-disorder (ADHD) among elementary school teachers in Saudi Arabia.Methodology: A cross-sectional study based on a structured questionnaire that was conducted onprimary school teachers in Saudi Arabia during 2023-2024. The questionnaire contains 51 questionsand is divided into three main parts. The first part is concerned with the social and personal data andcontains 15 questions. The second part is composed of 24 questions and is focusing on the level ofknowledge which might be high, moderate or low according to the score. The last part is to check theattitudes and contains 12 questions and according to the score the participant might have positive, fairor negative attitude. By using the following formula, n = (z)² p (1 – p) / d² the sample size is planned tobe 384. SPSS (Statistical-Package of Social -Science) version 20 will be used to analyze the data. Andthe data will be written by using “Microsoft Office Excel Software”.Result: The present study demonstrates a low level of knowledge among teachers regarding ADHD:about 94% had low level of knowledge. A positive association was found between knowledge level andthe teachers’ age, previous experience with ADHD and nationality (p value < 0.05). As regard attitude96% demonstrated a positive attitude towards ADHD.Conclusion: there is a low level of knowledge among teachers regarding ADHD, about 94% had lowlevel of knowledge while a significant majority of 96% demonstrated a positive attitude towards ADHD.Elementary school teachers should be trained in identifying ADHD symptoms as well as in behavioralmanagement and academic interventions